Assessing the Elimination of User Fees for Delivery Services in Laos - Boudreaux, Chantelle (Public Library of Science, 2015)
A pilot eliminating user fees associated with delivery at the point of services was introduced in two districts of Laos in March 2009. Following two years of implementation, an evaluation was conducted to assess the pilot impact, as well as to document the pilot design and implementation challenges. Study results show that, even in the presence of the substantial access and cultural barriers, user fees associated with delivery at health facilities act as a serious deterrent to care seeking behavior. We find a tripling of facility-based delivery rates in the intervention areas, compared to a 40% increase in the control areas. While findings from the control region suggest that facility-based delivery rates may be on the rise across the country, the substantially higher increase in the pilot areas highlight the impact of financial burden associated with facility-based delivery fees. These fees can play an important role in rapidly increasing the uptake of facility delivery to reach the national targets and, ultimately, to improve maternal and child health outcomes. The pilot achieved important gains while relying heavily on capacity and systems already in place. However, the high cost associated with monitoring and evaluation suggest broad-scale expansion of the pilot activities is likely to necessitate targeted capacity building initiatives, especially in areas with limited district level capacity to manage funds and deliver detailed and timely reports.